Analysis of the startegy acquisition of axis telekom indonesia by xl axiata - lessons for future acquisition strategy in indonesia telecom sector - Karima, Intan; Bobby Titus, Amol (The Indonesian Journal of Business Administration, 2018)
Abstract – To developed telecommunication industry, Indonesian government initiative to consolidate the industry for efficiency. The government is targeting that by 2019, just four telecommunication operators will be in operation. The future consolidation in the industry could involve mergers, acquisitions or expulsion from the industry. It is hoped that consolidation of the industry will enhance service quality and allow more competitive prices for consumers. In March 19, 2014, XL announced that the company has officially acquired PT Axis Telekom Indonesia (AXIS) with transaction value of US $865 million. As in the plan, XL set the main target of merger and acquisition was to get an additional 1800 MHz spectrum, where the spectrum is needed by XL to improve service quality and expand the company's network coverage. Although the acquisition process was successful, XL failed to meet its expectation when acquiring AXIS. There are three explanations that is most attributed: 1) Overpaying, 2) Overestimating synergies, and 3) Incomplete integration. As the lessons for future acquisition strategy in Indonesia telecom sector, the Author recommends to control cost strictly during implementation period in order to meet projected targets and not too much of debt as interest servicing will consume cash flow.Keywords: merger & acquisition, spectrum, telecommunication industry.